2021
DOI: 10.1136/gutjnl-2020-323609
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of the gut in undernutrition: what can technology tell us?

Abstract: Gut function remains largely underinvestigated in undernutrition, despite its critical role in essential nutrient digestion, absorption and assimilation. In areas of high enteropathogen burden, alterations in gut barrier function and subsequent inflammatory effects are observable but remain poorly characterised. Environmental enteropathy (EE)—a condition that affects both gut morphology and function and is characterised by blunted villi, inflammation and increased permeability—is thought to play a role in impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 152 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…These disadvantages-in conjunction with the lack of understanding of the role of the gut in the above conditions and diseases-demonstrate the need for noninvasive and reliable diagnostic tools to provide improved assessment and monitoring of intestinal permeability (and other aspects of gut function). [7][8][9] Recent clinical and preclinical studies have demonstrated that transcutaneous "through-theskin" fluorescence spectroscopy of orally ingested fluorescent contrast agents has the potential for noninvasive monitoring of gut permeability and other GI functions. [10][11][12][13][14][15] This approach entails subjects receiving an oral dose of a fluorescent contrast agent and a fluorescence sensing probe being placed on the skin to detect the permeation of that agent from the gut into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages-in conjunction with the lack of understanding of the role of the gut in the above conditions and diseases-demonstrate the need for noninvasive and reliable diagnostic tools to provide improved assessment and monitoring of intestinal permeability (and other aspects of gut function). [7][8][9] Recent clinical and preclinical studies have demonstrated that transcutaneous "through-theskin" fluorescence spectroscopy of orally ingested fluorescent contrast agents has the potential for noninvasive monitoring of gut permeability and other GI functions. [10][11][12][13][14][15] This approach entails subjects receiving an oral dose of a fluorescent contrast agent and a fluorescence sensing probe being placed on the skin to detect the permeation of that agent from the gut into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the specialized facilities required to perform the above-mentioned techniques and to analyze the collected samples are often unavailable in low-and middle-income countries (LMICs). As a result, improved diagnostic tools that provide noninvasive and reliable measurements of intestinal permeability (and other aspects of gut function) have the potential to introduce considerable clinical benefits [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To emphasize the importance of environmental enteropathy, the adverse functional impact (local or systemic) of environmental enteropathy, termed as environmental enteric dysfunction (EED), needs to be measured or identified. Although multiple domains of EED have been associated with biomarkers or functional tests of function [2], biomarkers and tests lack consistency and repeatability in different settings and the relationship to growth failure is uncertain [3]. This points towards considerable variation in EED phenotype and underlines the difficulty in defining EED without biopsies.…”
Section: Introductionmentioning
confidence: 99%